About Gabriel Derzhavin’s Poem Dedicated to Tsar Alexander I - Warda, Anna (W kręgu zagadnień języka, literatury i kultury: Księga jubileuszowa dedykowana Profesorowi Jarosławowi Wierzbińskiemu, 2022)
The subject of the article is a work of the famous poet of the turn of the 18th century, Gabriel Derzhavin. The work is dedicated to the favourite grandson of Catherine II, Alexander I. The poem is part of the so-called Felician cycle and is closely related to the moral and didactic fable, About Tsarevich Khlor, dedicated to Alexander I. Derzhavin’s poem does not only refer to the fairy-tale staffage but also shows a close relationship with the political and social reality of the time. The article also discusses the artistic value of this work, its content, and form.